Writing Aginst The Grain: The (re)presentation Of Historical Reality In Don Delillo's Libra (1988) - Hassiba, Soufli (جامعة الوادي - University of Eloued, 2021)
Abstract Don DeLillo’s Libra (1988), as a postmodernist historical novel, can be read as a subversive text that problematizes the boundary between historical reality and fiction. In fact, in Libra DeLillo, writing against the grain, seeks to question the truth-value of historical (re)presentation by imitating the traditional historical novel and corresponding to what Linda Hutcheon calls historiographic metafiction. As a historiographic metafiction, Libra does not only emphasize the indeterminacy of the meaning, but also it reflects that language is no longer the obedient servant of (re)presenting (writing/narrating) History. Therefore, this paper aspires to prove that Libra as a historiographic metafiction work challenges the capacity of history to represent reality outside the text and defy the truth-value of historical knowledge suggesting the possibility of plurality of truths instead of one truth.
Keywords: postmodernist historical novel; historical (re)presentation; historiographic metafiction; History; historical knowledge